A Landscape to Live by an Adaptation of Hardin Tibbs' Strategic Landscape: A Tool for Use in Facilitation Workshops. (March 2021) - Rose, Meg
The Strategic Landscape designed by Hardin Tibbs was originally produced for use as a tool to analyze the bigger picture ideas and ideals for better structure within businesses and societies. The focus of facilitation workshops is to uncover subconscious behavioral patterns and make individuals aware of their motivators so that they can make positive changes in their lives. The facilitation workshops incorporate critical thinking activities, encouraging individuals to further break down the many aspects of their lives with open-ended questions designed for personal insight, as well as group discussions around recognized behavior patterns and best practices. The Strategic Landscape contains easily recognized significant symbols. Individuals may separate the different aspects of their lives using this tool, to better recognize their activities and actions and analyze their desires. Through honest analysis of behavioral patterns and goal setting, individuals are afforded clarity in their lives. Here, we describe the adaptation of Hardin Tibbs' Strategic Landscape for use in facilitation workshops, to assist individuals to better structure their lives so that they may positively impact not only themselves but also their families, workplaces, and societies.